Hypokalemic paralysis due to distal renal tubular acidosis type 1 in patient of mucormycosis on amphotericin B: a case report - Shah, Mohita; Kothari, Prafful (International Journal of Advances in Medicine, 2022)
A 42-year-old male patient who is a known case of DM and mucormycosis on treatment presented with sudden onset difficulty in moving all 4 limbs followed by decreased depth of respiration for 4 hours. The patient was known case of DM for 10 years and was on OHA for the same, he had history of biopsy diagnosed rhino mucormycosis 4 months ago and was on treatment for the same. On initial examination the tone was hypotonic in all4 limbs along with power of 3+, respiration was shallow and patient was bedridden unable to stand on his own, he was ambulatory 6 days before presenting to hospital. Potassium-1.7 mEq/l, ABGA pH-7.18, HCO3-10 Meq/l, urine osmolality 220 mOsm/l, urine pH-7.0, potassium-to-creatinine rstio (K/Cr)-3.9 mEq/ml, urine K-22 mEq/ml. Distal RTA (dRTA) is the classical form of RTA, being the first described. Distal RTA is characterized by a failure of H+ secretion into lumen of nephron by the alpha intercalated cells of the medullary collecting duct of the distal nephron. This failure of acid secretion may be due to a number of causes, and it leads to an inability to acidify the urine to a pH of less than 5.3. This case study enumerates the potentially dangerous side effects of amphotericin B in patients which can precipitate RTA type 1 leading to severe hypokalaemia and acidosis, thus all patients receiving amphotericin B should be cautiously warned regarding side effect of hypokalaemia and prophylactic potassium syrup supplementation may be given in predisposed patients.